A prática docente de uma professora da Educação Infantil e seus desafios - Coan, Adriana Aparecida (2017)
This research aims to reflect on the effectiveness of the instruments of planning and implementation of Pedagogical political project through the eyes and actions of the teacher, the initial training, in-service training and planning activities. The methodological path chosen contemplates the qualitative research, choosing the case study, and opting for a teacher like our subject of study. We use as documentary analysis procedures with all the documents used in the survey until here explained and semi-structured interview-with the testimony of a teacher, who is the subject of research. The subject was a teacher of a private and pre- school in São Paulo. As a result it was possible to understand the role of the teacher, to be active in day by day classroom and reflecting on their practice in the exchange between pairs. In the course of the study was clear conception of a re- signification childhood, children's education is no longer a place for assistance and turned into an educational space, bringing concerns relating to the process of development of children. In this new scenario the teacher is considered the mediator that aims, through a job, based on reflections and construction of your planning on the basis of the ideas brought by the pedagogical political plan and the school's education plan, articulate meaningful, contextualized learning that bring meaning and personal, social and cognitive development, critical and emancipatory perspective. In this way, the pedagogical practice can be viewed as a process of training, upgrading, reflectioning, contextualizing of teaching practice in school. Under the watchful eye and attentive listening to the best interests of the child, considering the historical protagonist and a subject of their learning. On several theoretical, ideological trends and best practices, it was observed that the teacher, accompanied by a coordinator and under the continuous training in service, by pairs, leading a linked to criticality and emancipation of their actions at school, straightforward consistency between theory and practice in its operations